Kidney Injury and Electrolyte Abnormalities in Liver Failure - Bonavia, Anthony; Singbartl, Kai (Seminars in Respiratory and Critical Care Medicine, 2018)
The liver and kidney are key organs of metabolic homeostasis in the body and display complex interactions. Liver diseases often have direct and immediate effects on renal physiology and function. Conversely, acute kidney injury (AKI) is a common problem in patients with both acute and chronic liver diseases. AKI in patients with acute liver failure is usually multifactorial and involves insults similar to those seen in the general AKI population. Liver cirrhosis affects and is directly affected by aberrations in systemic and renal hemodynamics, inflammatory response, renal handling of sodium and free water excretion, and additional nonvasomotor mechanisms. Subsequent problems, for example, worsening ascites, hyponatremia, and AKI, often complicate management of patients with chronic progressive liver disease and add to their morbidity and mortality. Thus, AKI must be carefully defined and diagnosed in patients with liver disease. The kidney also plays a pivotal role in balancing acid–base disturbances resulting from advanced liver disease, making AKI in the setting of end-stage liver disease very difficult to manage clinically. While renal dysfunction in these patients often resolves following orthotopic liver transplant, dialysis may be required as a bridge to transplantation to mitigate the metabolic disarray found in these critically ill patients.
Keywords: acute kidney injury; acute liver failure; chronic liver disease; hepatorenal syndrome